Influence of the welding sequence on residual stress and distortion of fillet welded structures. (March 2016) - Fu, Guangming; Lourenço, Marcelo Igor; Duan, Menglan; Estefen, Segen F.
Abstract: T-joints are one of the most common welded joints used in the construction of offshore structures, including ships and platforms. In the present study, a sequentially coupled thermo-mechanical finite element model that considers temperature-dependent material properties, high temperature effects and a moving volumetric heat source was used to investigate the effect of welding sequence on the residual stresses and distortions in T-joint welds. The parameters of Goldak's double ellipsoidal heat source model were predicted using a neural network. The numerical models were successfully validated by the experimental tests. The results show that the welding sequences have significant effects on the residual stresses and distortions, both in the magnitude and distribution mode. The optimization of the welding sequences should be investigated numerically or experimentally before the construction welded structure. Highlights: Welding imperfections of T-joint are investigated under the various welding sequences. Residual stress is concentrated near the weld start/end locations. Welding sequence significantly influences the magnitude and deformation mode of the deflections. Single-side welding sequence causes more distortion.